Tipologi atap bangunan berkonstruksi kayu pada relief Candi Borobudur - Hari Setyawan (Berkala Arkeologi, 2022)
Borobudur is a Buddhist temple which represents the pinnacle of the ancient Javanese civilization in the VIII–IX centuries CE.  One of the most significant architectural ornament attributes at Borobudur Temple is the narrative reliefs. This paper discusses the typology of the wooden constructions based on the roof depicted on the reliefs. This study uses an analytical descriptive method which groups wooden buildings based on the shape of the roof, to be used as elements in the design of buildings and facilities for settlements related to the preservation of the Borobudur area as a Cultural World Heritage. The results show that there are at least six types of wooden construction based on the shape of the roof. These buildings in the Old Javanese period could function as houses, barns, halls, buildings in palace complexes, dormitories, monasteries, and auxiliary buildings in settlements.